Unique identification code for medical fundus images using blood vessel pattern for tele-ophthalmology applications. Issue 135 (October 2016) - Singh, Anushikha; Dutta, Malay Kishore; Sharma, Dilip Kumar
Highlights: The proposed work presents an accurate method for generation of unique identification code for tele-ophthalmology applications. Strategic combination of unique blood vessel pattern and patient ID is considered to generate of unique identification code. At the diagnosis centre, patient ID is accurately recovered from the unique identification code for integrity verification. The proposed method is tested on the publically available data base of fundus image and results are encouraging. Abstract: Background and objective: Identification of fundus images during transmission and storage in database for tele-ophthalmology applications is an important issue in modern era. The proposed work presents a novel accurate method for generation of unique identification code for identification of fundus images for tele-ophthalmology applications and storage in databases. Unlike existing methods of steganography and watermarking, this method does not tamper the medical image as nothing is embedded in this approach and there is no loss of medical information. Methods: Strategic combination of unique blood vessel pattern and patient ID is considered for generation of unique identification code for the digital fundus images. Segmented blood vessel pattern near the optic disc is strategically combined with patient ID for generation of a unique identification code for the image. Results: The proposed method of medical image identification is tested on the publically available DRIVE and MESSIDOR database of fundus image and results are encouraging. Conclusions: Experimental results indicate the uniqueness of identification code and lossless recovery of patient identity from unique identification code for integrity verification of fundus images.